2023
DOI: 10.3390/ijms24108794
|View full text |Cite
|
Sign up to set email alerts
|

JAC4 Inhibits EGFR-Driven Lung Adenocarcinoma Growth and Metastasis through CTBP1-Mediated JWA/AMPK/NEDD4L/EGFR Axis

Abstract: Lung adenocarcinoma (LUAD) is the most common lung cancer, with high mortality. As a tumor-suppressor gene, JWA plays an important role in blocking pan-tumor progression. JAC4, a small molecular-compound agonist, transcriptionally activates JWA expression both in vivo and in vitro. However, the direct target and the anticancer mechanism of JAC4 in LUAD have not been elucidated. Public transcriptome and proteome data sets were used to analyze the relationship between JWA expression and patient survival in LUAD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…To evaluate the potential of JWA as a therapeutic target for PD, we employed JAC4, a compound designed to activate JWA by enhancing its expression [ 21 ]. JAC4 treatment demonstrated effectiveness in elevating JWA expression across various tissues, encompassing the intestine, lung, and brain [ 21 , 38 , 39 ]. In line with these observations, our study revealed a significant increase in JWA expression in primary neurons and the midbrain of mice upon JAC4 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the potential of JWA as a therapeutic target for PD, we employed JAC4, a compound designed to activate JWA by enhancing its expression [ 21 ]. JAC4 treatment demonstrated effectiveness in elevating JWA expression across various tissues, encompassing the intestine, lung, and brain [ 21 , 38 , 39 ]. In line with these observations, our study revealed a significant increase in JWA expression in primary neurons and the midbrain of mice upon JAC4 treatment.…”
Section: Discussionmentioning
confidence: 99%